Multicenter randomized, open‐label phase II trial of sequential erlotinib and gemcitabine compared with gemcitabine monotherapy as first‐line therapy in elderly or ECOG PS two patients with advanced NSCLC. Issue 1 (27th February 2014) - Michael, Michael; White, Shane C; Abdi, Ehtesham; Nott, Louise; Clingan, Phillip; Zimet, Allan; Button, Peter; Gregory, Daniel; Solomon, Benjamin; Dobrovic, Alexander; Do, Hongdo; Clarke, Stephen
Abstract Aim The potential beneficial interaction between erlotinib and chemotherapy may require sequencing or pharmacodynamic separation. The aim of this study was to evaluate the efficacy and tolerance of sequential erlotinib and gemcitabine versus gemcitabine monotherapy as first‐line therapy in elderly or ECOG PS‐2 patients with advanced non‐small cell lung carcinoma. Methods The primary objective of this multicenter randomized Phase II study was progression‐free survival (PFS). Secondary objectives were overall response rate (ORR), disease control rate, response duration, overall survival and safety. Patients were randomized to either gemcitabine (1250 mg/m2 Day 1, 8 q28 days) followed by erlotinib (150 mg/day on day 15 through day 28), (EG‐arm), or gemcitabine monotherapy (1000 mg/m2 Days 1, 8, 15 q28 days), (G‐arm) for up to six cycles. Results Fifty‐four patients were recruited, 28 G‐arm and 26 EG‐arm. Overall, efficacy results were not significantly different between study arms. Median PFS and ORR for the G‐ versus EG‐arms were 8.0 versus 10.3 weeks (hazard ratio 1.3; 95% confidence interval [0.63;2.68]; P = 0.48) and 7.1 versus 3.8 percent respectively (difference −3.30; 95% confidence interval [−17.5;10.9]). The majority of adverse events (AEs) in both arms were Grade 1–2. The commonest AEs recorded in the EG‐ and G‐arms were rash‐like events (65 percent) and nausea (42 percent) respectively. Four patients (17 percent) in EG‐arm and five (16 percent) in G‐arm experienced at least one treatment‐related serious AE. Conclusions In this study, patients with non‐small cell lung carcinoma at ECOG PS‐2 or aged ≥70 years derived no efficacy advantage from sequential erlotinib in combination with gemcitabine relative to gemcitabine alone. No unexpected safety findings were noted.